Heparanase 1 involvement in prostate physiopathology. (5th April 2017) - Barbosa, Guilherme O.; Cervigne, Nilva K.; Carvalho, Hernandes F.; Augusto, Taize M.
Abstract: The prostate is a compound exocrine gland of the male reproductive tract universally present in mammals. It is highly responsive to androgen and can be committed by a variety of pathological complications as prostatitis, benign, and malignant proliferative changes, which may be intensified by aging. Prostate intensively turnover its extracellular matrix (ECM) either at homeostasis or disease which includes a dynamically change of glycosaminoglycan composition during the life of an individual. Among the different enzymes playing a role in such changes, heparanase‐1 is responsible for cleaving heparan sulfate (HS) at a limited number of sites, clearly involved in tissue remodeling. Its activity has been strongly implicated in cell invasion associated with cancer metastasis, a consequence of the structural modification that loosens the ECM barrier. In the present review we focuses in some aspects of the prostate physiology and diseases, particular prostate cancer, evidencing how the HPSE‐1 activity encompasses the relationship of both processes.